Importance of ventilation and occupancy to Mycobacterium tuberculosis transmission rates in congregate settings - A. K. Deol; N. Shaikh; K. Middelkoop; M. Mohlamonyane; R. G. White; N. McCreesh (BMC Public Health, 2022)
Abstract Background Ventilation rates are a key determinant of the transmission rate of Mycobacterium tuberculosis and other airborne infections. Targeting infection prevention and control (IPC) interventions at locations where ventilation rates are low and occupancy high could be a highly effective intervention strategy. Despite this, few data are available on ventilation rates and occupancy in congregate locations in high tuberculosis burden settings. Methods We collected carbon dioxide concentration and occupancy data in congregate locations and public transport on 88 occasions, in Cape Town, South Africa. For each location, we estimated ventilation rates and the relative rate of infection, accounting for ventilation rates and occupancy. Results We show that the estimated potential transmission rate in congregate settings and public transport varies greatly between different settings. Overall, in the community we studied, estimated infection risk was higher in minibus taxis and trains than in salons, bars, and shops. Despite good levels of ventilation, infection risk could be high in the clinic due to high occupancy levels. Conclusion Public transport in particular may be promising targets for infection prevention and control interventions in this setting, both to reduce Mtb transmission, but also to reduce the transmission of other airborne pathogens such as measles and SARS-CoV-2.